The Panginyongan Film Identity: Narrative and Cinematic Approaches of Local Cinema - Ferdinanda; Guntur; Ranang Agung Sugihartono (INJECT (Interdisciplinary Journal of Communication), 2025)
This study examines how narrative and cinematic constructions in the short films of Banyumas Raya, Indonesia, contribute to the formation of a distinct Panginyongan film identity. Focusing on three fictional film works, Dolanan Layangan, Pur, and SETAN: Seni Tani, this research employs a qualitative content analysis method grounded in Bordwell's film concept, integrated with theories of realism (Bazin), creative improvisation (Sawyer), and identity representation (Hall). The findings reveal a synergistic construction of identity through three interconnected themes: (1) narratives centered on everyday conflicts resolved through communal values, (2) a realist-improvisational aesthetic using long takes, natural lighting, and non-professional actors to achieve authenticity, and (3) the use of the Ngapak language and local cultural symbols as markers of identity and symbolic resistance. The study concludes that these films function not merely as cultural representations but as active sites of identity negotiation. Furthermore, it proposes a Panginyongan Film Identity Model that synthesizes these elements, offering a framework for understanding similar practices in other Indonesian regional cinemas. This research underscores the significance of local cinema as a vital cultural practice that challenges mainstream aesthetics and contributes to Indonesia's diverse national cinematic landscape.